Knowledge diffusion and knowledge transfer: two sides of the medal - Torben Klarl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Understanding the way in which knowledge is technically produced and transferred, and how its diffusion path can be characterized is of fundamental importance for the performance of an economy. Although this fact seems to be plausible ex ante, the relevant literature so far has paid less attention investigating the microeconomic link between knowledge transfer and knowledge diffusion in a comprehensive approach. The aim of this paper is to highlight the link between knowledge transfer, knowledge diffusion and network effects in a stochastic environment, because the adoption decision of new knowledge should be treated as a stochastic event. For this reason, a new knowledge diffusion model in the line of Bass (1969) has been put forward, which integrates knowledge diffusion and knowledge transfer. The advantage of the proposed model is twofold. From a theoretical point of view, not only the so-called unimodal diffusion phenomena can be modelled, but also bimodal diffusion phenomena can be obtained. From an empirical point of view, the model which incorporates heteroscedastic errors and mean reverting behaviour can be theoretically estimated directly within a standard SUR context.
Keywords: C50; C51; C61; D89; 330; Knowledge diffusion; knowledge transfer; SUR; Wissen; Innovationsdiffusion; Wissenstransfer; Network Externalities; Wirtschaftsmodell; Theorie